2014
DOI: 10.1159/000357411
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 16 Abnormalities in Embryos and in Sperm from a Male with a Fragile Site at 16q22.1

Abstract: Two fragile sites, FRA16B and FRA16C, are located in the chromosome band 16q22.1. Neither of them is associated with any specific clinical condition. We report the development and outcome of a clinically applied PGD cycle in a couple who had difficulty in achieving pregnancy. The woman was a carrier of a balanced reciprocal translocation, t(11;22)(q23;q11.2), and the man presented high expression of the fragile site 16q22.1 (FRA16B/C) in peripheral blood lymphocytes. Gains and losses of chromosome 16 fragments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Fragility at 16q22 has since been implicated in a wide spectrum of neurological disorders (Demirhan et al 2006; Kerbeshian et al 2000) as well as in other conditions such as neutropenia (Glasser et al 2006; Tassano et al 2010) and cleft palate (Bettex et al 1998; Dunner et al 1983; Janiszewska-Olszowska et al 2013; McKenzie et al 2002). A recent study also reported elevated fragile site formation at 16q22.1 in an embryo from a couple who had difficulty achieving pregnancy and in the sperm from the father (Martorell et al 2014). However, cytogenetic breakage and potential disease-associated gene(s) at this locus are yet to be molecularly characterized.…”
Section: 2 Early History Of Chromosome Fragile Site Discoveries Rementioning
confidence: 85%
“…Fragility at 16q22 has since been implicated in a wide spectrum of neurological disorders (Demirhan et al 2006; Kerbeshian et al 2000) as well as in other conditions such as neutropenia (Glasser et al 2006; Tassano et al 2010) and cleft palate (Bettex et al 1998; Dunner et al 1983; Janiszewska-Olszowska et al 2013; McKenzie et al 2002). A recent study also reported elevated fragile site formation at 16q22.1 in an embryo from a couple who had difficulty achieving pregnancy and in the sperm from the father (Martorell et al 2014). However, cytogenetic breakage and potential disease-associated gene(s) at this locus are yet to be molecularly characterized.…”
Section: 2 Early History Of Chromosome Fragile Site Discoveries Rementioning
confidence: 85%
“…Previous case report and clinical study both indicated that embryos from mosaic fragile carriers have certain ratio of dup or del chromosome which is related with its fragile sites. 21,22 Luo et al studied 12 couples with heterozygous mosaic fragile 16q22 on their chromosomes. These couples underwent preimplantation genetic testing for their embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Aswini reported a non-consanguineous couple with repeated pregnancy loss who presented with FRA16B expression (Aswini et al, 2012). Recently, Martorell reported a couple with difficulty achieving pregnancy, where the wife was a carrier of t(11;22) (q23;q11.2) and the husband had a high expression of fragile site at 16q22.1 (FRA16B/C) in his peripheral blood lymphocytes (Martorell et al, 2014). The husband's sperm and the embryos both showed chromosome 16 abnormalities, indicating that the fragile site at 16q22.1 might cause chromosomal disorders involving the same breakpoint and non-disjunction during meiosis, thereby leading to pregnancy losses.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome 16q22.1 contains two fragile sites, FRA16B and FRA16C (Martorell et al, 2014). Previously, these fragile sites were not associated with either clinical problems or phenotypic effects (Schmid et al, 1986).…”
Section: Discussionmentioning
confidence: 99%